Multifunctional interaction of CihC/FbpC orthologs of relapsing fever spirochetes with host-derived proteins involved in adhesion, fibrinolysis, and complement evasion - Damm, Ann-Sophie; Reyer, Flavia; Langhoff, Luisa; Lin, Yi-Pin; Falcone, Franco Harald; Kraiczy, Peter (Frontiers in Immunology, 2024)
Introduction Relapsing fever (RF) remains a neglected human disease that is caused by a number of diverse pathogenic Borrelia (B.) species. Characterized by high cell densities in human blood, relapsing fever spirochetes have developed plentiful strategies to avoid recognition by the host defense mechanisms. In this scenario, spirochetal lipoproteins exhibiting multifunctional binding properties in the interaction with host-derived molecules are known to play a key role in adhesion, fibrinolysis and complement activation. Methods Binding of CihC/FbpC orthologs to different human proteins and conversion of protein-bound plasminogen to proteolytic active plasmin were examined by ELISA. To analyze the inhibitory capacity of CihC/FbpC orthologs on complement activation, a microtiter-based approach was performed. Finally, AlphaFold predictions were utilized to identified the complement-interacting residues. Results and discussion Here, we elucidate the binding properties of CihC/FbpC-orthologs from distinct RF spirochetes including B. parkeri, B. hermsii, B. turicatae, and B. recurrentis to human fibronectin, plasminogen, and complement component C1r. All CihC/FbpC-orthologs displayed similar binding properties to fibronectin, plasminogen, and C1r, respectively. Functional studies revealed a dose dependent binding of plasminogen to all borrelial proteins and conversion to active plasmin. The proteolytic activity of plasmin was almost completely abrogated by tranexamic acid, indicating that lysine residues are involved in the interaction with this serine protease. In addition, a strong inactivation capacity toward the classical pathway could be demonstrated for the wild-type CihC/FbpC-orthologs as well as for the C-terminal CihC fragment of B. recurrentis. Pre-incubation of human serum with borrelial molecules except CihC/FbpC variants lacking the C-terminal region protected serum-susceptible Borrelia cells from complement-mediated lysis. Utilizing AlphaFold2 predictions and existing crystal structures, we mapped the putative key residues involved in C1r binding on the CihC/FbpC orthologs attempting to explain the relatively small differences in C1r binding affinity despite the substitutions of key residues. Collectively, our data advance the understanding of the multiple binding properties of structural and functional highly similar molecules of relapsing fever spirochetes proposed to be involved in pathogenesis and virulence.